Self-esteem victims of bullying in grade 4 students at SDN Tububesak Timor Tengah Selatan Nusa Tenggara Timur - Yustrivat Asa (Jurnal Psikologi Tabularasa, 2023)
Bullying behavior in South Central Timor and East Nusa Tenggara is still increasing from year to year, which continues to have psychological effects on victims whose suffering is unimaginable. This study aims to explore the psychological effects of victims, namely self-esteem, on elementary school students. This study uses qualitative methods with data collection techniques using interviews and observation. The data analysis technique used is descriptive-qualitative. The research subjects for class 4 of the public elementary school in Tububesak, South Central Timor, consisted of 10 students, consisting of 6 boys and 4 girls aged 10–11 years. The results of this study indicate that the male and female students experienced a decrease in self-esteem in the outer self (appearance and popularity), relational self (family and community members), and personal self (achievement, intelligence, and abilities). Especially in the aspect of relational self (closeness to God), all students feel hope to continue to live.Perilaku bullying di TTS NTT masih mengalami peningkatan dari tahun ke tahun yang terus menerus memberikan efek psikologis bagi korban yang tidak terbayangkan penderitaanya. Penelitian ini bertujuan untuk mendalami efek psikologis korban yaitu harga diri pada siswa SD. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data menggunakan wawancara dan observasi. Teknik Analisa data yang digunakan yaitu teknik deskriptif kualitatif. Subjek penelitian kelas 4 Sekolah Dasar Negeri di Tububesak Timor Tengah Selatan berjumlah 10 siswa terdiri dari 6 orang lakilaki dan 4 orang perempuan berusia 10-11 Tahun. Hasil penelitian ini menunjukan bahwa siswa laki-laki dan perempuan mengalami penurunan harga diri pada aspek Outer self (penampilan dan popularitas), relational self (keluarga dan anggota masyarakat) dan personal self (prestasi, kecerdasan, dan kemampuan). Terkhusus pada aspek relational self (kedekatan dengan Tuhan) seluruh siswa merasakan harapan untuk tetap terus hidup